Regional Unemployment and Norm-Induced Effects on Life Satisfaction - Adrian Chadi (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
While rising unemployment generally reduces people's happiness, researchers argue that there is a compensating social-norm effect for the unemployed individual, who might suffer less when it is more common to be unemployed. This empirical study, however, rejects this thesis for German panel data and finds individual unemployment to be even more hurtful when aggregate unemployment is higher. On the other hand, an extended model that separately considers individuals who feel stigmatised from living off public funds yields strong evidence that this group of people does in fact suffer less when the normative pressure to earn one's own living is lower.
Keywords: I3; J6; 330; social norms; unemployment; well-being; social benefits; labour market policies; Regionaler Arbeitsmarkt; Zufriedenheit; Arbeitslosigkeit; Sozialpsychologie; Panel; Schätzung; Deutschland